A concepção literária e simbólica encontrada nas Canciones de Federico García Lorca: estudo de casos - Lara, Idalmo Mendes (2009)
This work belongs to the domain of the research field of Poetics of the Literary Text and investigates the poetics of Federico García Lorca, exponent of the Spanish and universal literature, by analyzing poems from his book entitled Canciones. In order to examine the musical sensitivity of the poet to compose verses, five poems were selected from Canciones. This research makes an interpretation of the poetics of the Federico García Lorca by identifying the incidence of the thematic, structural and rhythmical patterns and also the incidence of symbolic patterns and their implications in the poetics of Lorca. Several authors have been studied in order to elucidate the scope of the term canção ; to show its essential characteristic, to scan and to classify the type of verse used in Lorca s poetry, as well as to capture the images, symbols and meanings of his poetry. Among the results obtained, the research shows, in its formal aspect, some common points in the selected poems such as refrains, couplets, squares and sextiles; and also some different points, as the structure of the stanzas. As far as the verses are concerned, it was detected the predominance of verses of eight syllables (octossílabos), of long and short redondilhas (verses of five or seven syllables), as well as other types of verses, also of considerable musical effect. Regarding the theme, the results of this research confirm the importance of the aspects related to the universe of children, to the attributes of nature and to the presence of death. Concerning the symbolic aspects, common elements related to images of brightness, cornus, eye, clouds and wings have been discovered. Such elements are associated with the verticality of human being and with the symbols of the ascendancy of the heroic structures, belonging to the diurnal regime of the imaginary. With reference to the musicality, there have been identified some special procedures to deal with syllables, words and verses related to musical, theatrical, choreographical and poetical composition within the five selected poems. And, finally, this work speculates about a possible structure of musicality on Lorca s poems recitations.